DAUN Alphitonia incana (Roxb.) Teijsm. & Binn. ex Kurz SEBAGAI ANTI-Escherichia coli: STUDI IN SILICO DAN IN VITRO - Ramadhan, Hafiz; Forestryana, Dyera; Jamaludin, Wahyudin Bin; Hadi, Ahmad Nur; Raudatunnisa (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
This research was conducted to determine the potential of phytochemical contents in producing antibacterial activity from 70% ethanol extract of Balik Angin leaves (Alphitonia incana (Roxb.) Teijsm . & Binn. ex Kurz) against Escherichia coli bacteria in silico and in vitro. In silico assay of 20 compounds contained in Alphitonia species against the DNA gyrase receptor using PLANTs. Anti-E.coli activity assay of Balik Angin leaves macerated with 70% ethanol solvent using the Well diffusion method. In silico studies show that β-Sitosterol, Stigmasterol, Rutin, Kaempferol 3-O-rutinoside, and Zizyphoiside C have binding energies with DNA gyrase that can exceed Ciprofloxacin. The antibacterial assay results at a highest concentration of 26.56 mg/ml can provide an average inhibitory zone diameter of 12.75 ± 0.2 mm with a minimum inhibitory concentration (MIC) of 1.66 mg/ml (5.87 ± 1.5 mm). The 70% ethanol extract of Balik Angin leaves has the potential as an anti-Escherichia coli, supported by the content of phytochemical compounds that can act as DNA gyrase inhibitors.